Effect of guided discovery learning model based on lesson study learning community on the chemistry of main group elements topics - Miftahul Jannah; Dita Yumarni Lase; Yolanda Putri; Nofrianto Nofrianto; Lydia Aryani; Andromeda Andromeda (Jurnal Pijar Mipa, 2023)
According to the students of senior high school SMAN 14 Padang, chemistry is one of the most challenging subjects. It causes the learning process in the classroom to be teacher-centered. Therefore, a suitable learning model is needed so that students are active in finding information to create student-centered learning. One of the appropriate learning models used is Guided Discovery learning with the lesson study learning community LSLC learning system. This study aims to determine the effect of the guided discovery learning model based on LSLC on the chemistry of main group elements on student learning outcomes at SMAN 14 Padang. The type of research used is a quasi-experiment. In this study, two classes were used, namely the experimental and control classes, with a simple random sampling technique. In the experimental class XII MIPA 2, the special treatment was applying a Guided discovery learning model based on LSLC on the chemistry of the main group elements. In the control class XII MIPA 3 without LSLC based. The data analysis techniques used were the N-Gain test, normality test, homogeneity test, hypothesis test, and hypothesis testing with t-test. The results showed that in the experimental class, there was an increase in student learning outcomes in the moderate category with an average N-Gain value of 0,6999. In the control class, the average value was 0,6168. It also shows that in the control class, there is an increase in student learning outcomes in the moderate category. The results of data analysis with the normality test and homogeneity test that have been carried out obtained that the data is normally distributed and homogeneous, so hypothesis testing is carried out with the t-test. The learning outcomes of students who apply the guided discovery learning model based on LSLC can be significantly improved than those without LSLC based on the main group element chemical material at SMAN 14 Padang.